Perancangan Sistem Pengukuran Kinerja Dengan Metode Balanced Scorecard (Studi Kasus BUMD ABC Kota Bogor) - Deni Sakri Harumantaka; Idqan Fahmi; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Along with the implementation of provisions related to the regional-owned company in Bogor City Government, Regional Company ABC (the Company) took the initiative to design a precise and measurable performance measurement system. This study aims to manifest and portray the Company’s vision, mission, and motto into strategic objectives, to determine key performance indicators, and to design a performance evaluation system based on Balanced Scorecard (BSC). Data were collected by structured questionnaires, interviews, and Focus Group Discussion (FGD) to the directors and structural management as respondents based on non-random sampling methods. The strategic analysis (i.e., SWOT matrix, external-internal matrix, QSPM) was employed to assess operational excellence, business growth, and customer loyalty as the company's strategic objectives. As a result, we found fourteen performance indicators for the Company based on the BSC. The indicator targets were in line with the Company’s Budget Plan and the provisions of the Board of Directors. The design of this assessment system was then outlined in the form of an evaluation working paper as guidelines for the Company in running its business.Keywords: balanced scorecard, performance, measurement, regional company, SWOTAbstrak: Seiring dengan penerapan ketentuan terkait perusahaan daerah di wilayah Pemerintahan Kota Bogor, BUMD ABC (Perseroan) berinisiasi untuk merancang sistem pengukuran kinerja yang tepat dan terukur. Penelitian ini bertujuan menerjemahkan dan memetakan visi, misi, dan moto Perseroan ke dalam tujuan strategis, menentukan indikator keberhasilan kinerja, dan merancang sistem penilaian kinerja Perseroan berdasarkan Balanced Scorecard (BSC). Data dikumpulkan melalui kuesioner terstruktur, wawancara, dan Diskusi Kelompok Terpumpun (DKT) dengan direksi dan pejabat struktural Perseroan menjadi responden penelitian melalui pengumpulan sampel tidak acak. Data kemudian diolah dengan alat analisis manajemen strategis (matriks SWOT, matriks internal eksternal, QSPM). Hasilnya adalah dalam proses perancangan dengan analisis, faktor keunggulan operasional, pertumbuhan usaha, dan loyalitas pelanggan menjadi tujuan strategis perusahaan yang ingin dicapai. Terdapat empat belas indikator kinerja yang tepat bagi Perseroan berdasarkan BSC dengan target yang selaras dengan RKAP dan ketentuan Dewan Direktur. Rancangan sistem penilaian ini kemudian dituangkan dalam bentuk kertas kerja evaluasi sebagai panduan bagi Perseroan dalam menjalankan bisnisnya.Kata kunci: balanced scorecard, BUMD, kinerja, pengukuran, SWOT